Teste de escolha entre diferentes frutos pela mosca-da-fruta Zaprionus indianus Gupta, 1970 (Diptera: Drosophilidae) - Bueno, Isabella [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This study analyzed the oviposition behavior of Zaprionus indianus, a fly belonging to Drosophilidae family that was first detected in Brazil in 1999. The fly, supposedly of African origin, was accidentally introduced, becoming Ficus carica L plague, a purple fig species widely cultivated in the city of Valinhos, São Paulo state. Since the introduction of pest species, a significant loss in production of the purple fig occurred, as the fly lays its eggs in the fig ostiole, making it unfit for human consumption. This caused considerable economic damage, as Brazil is one of the ten largest fig producers in the world. Tests involving oviposition choice between three different fruits were performed. The fruits used were khaki mango and guava, combined two by two in three tests with ten replicates each. These fruits were chosen because they are often grown under the same property or properties in the vicinities of fig producers, and can be used as substrate for oviposition in purple fig intercrop. In each replication, the fruits were exposed two by two, separated by a distance of 30cm. Replicas remained in climatic chambers (Eletrolab, EL 202) for a period of 10 hours, with temperature and light controlled. From this, it performed the counting of eggs in each fruit and applied the z ratios test (Zar, 1999), to assess whether there was a statistically significant preference for a particular fruit. Statistically, there was a significant preference for khaki both in the test between khaki and mango as in the test between khaki and guava . In the third test, mango and guava, there was not significant preference for one of the fruits. Taking into account this information, it was possible to subsidize the development of more efficient control techniques for fly populations. Beyond the control of this species in purple fig, the results obtained suggest that producers should be alert with the possible infestation...

Esse trabalho visou analisar o comportamento de oviposição da espécie Zaprionus indianus, mosca pertencente à família Drosophilidae que foi constatada pela primeira vez no Brasil em 1999. A mosca, supostamente de origem africana, foi introduzida acidentalmente, tornando-se praga de Ficus carica L, uma espécie de figo-roxo amplamente cultivada no município de Valinhos, SP. A partir da introdução dessa espécie-praga, houve um significativo prejuízo na produção do figo-roxo, já que a mosca deposita seus ovos no ostíolo do figo, tornando-o impróprio para o consumo humano. Isto acarretou um prejuízo econômico considerável, já que o Brasil é um dos dez maiores produtores de figo do mundo. Testes envolvendo escolha de oviposição entre três diferentes frutos foram realizados. Os frutos utilizados foram caqui, manga e goiaba, combinados dois a dois, em três testes, com dez réplicas cada. Esses frutos foram escolhidos, porque são frequentemente cultivados nas mesmas propriedades ou em propriedades vizinhas às dos ficicultores, e podem ser utilizados como substrato para oviposição na entressafra do figo-roxo. Em cada réplica, os frutos foram expostos dois a dois, separados por uma distância de 30cm. As réplicas permaneceram em câmaras climáticas (Eletrolab, EL 202) por um período de 10 horas, com temperatura e luminosidade controladas. A partir disso, foi realizada a contagem dos ovos em cada fruto e aplicado o teste z de proporções (ZAR, 1999), para avaliar se houve preferência estatisticamente significativa por um determinado fruto. Estatisticamente, houve preferência significativa pelo caqui, tanto no teste entre caqui e manga como no teste entre caqui e goiaba. No terceiro teste, manga e goiaba, não houve preferência significativa por um dos frutos. Levando em consideração essas informações, foi possível conhecer melhor a preferência de oviposição da espécie...
Keywords: Diptero; Ovo - Implantação; Mosca; Drosofila; Figo; Pragas agricolas - Controle; Diptera